Effectiveness of polyhexamethylene biguanide dressings vs. platelet-rich plasma in diabetic foot ulcer: a pilot study of case series - Martínez-Mejorada, Roerto; Rojas-Ortiz, Jorge A.; López-Romero, Sandra C.; Vázquez-Guerra, Ximena C.; Gonzalez, Gabriel Garcia (International Journal of Research in Medical Sciences, 2024)
Diverse treatments, including polyhexamethylene biguanide dressings, have been explored for managing diabetic foot ulcers. Platelet-rich plasma, known for its potential in chronic wound healing, has demonstrated efficacy both in vivo and in vitro, with possible intralesional or topical application. However, research on the production costs of PRP is scarce. This study compares the effectiveness and financial implications of polyhexamethylene biguanide dressings versus Platelet-rich Plasma in the treatment of diabetic foot ulcers. Conducted at the General Hospital of Mexico from July to August 2019, this case series involved 8 patients, split equally between the two treatment groups. Weekly assessments showed consistent reductions in wound size in both groups. By the fourth week, 75% of patients achieved clinical healing. The PHMB group demonstrated a 75.13% reduction in wound size, compared to a 37.38% reduction in the PRP group. However, due to the small sample size, no statistical significance was found between wound size, healing time, and dressing type. This report suggests no clear relationship between treatment, healing duration, and wound diameter. Additionally, PRP did not show a clear financial advantage over PHMB dressings. Randomized control trials with sufficient sample sizes are required to demonstrate overall advantage for each therapy choice.